(untitled) (Journal of the College of Basic Education, 2022)
The effects of γ- ray on the Dispersion Parameters of (PMMA) films, prepared by using casting technique, are studied by using Cauchy, Sellmeier and Wemple-DiDomenico models. Other optical parameters like Carrier concentration and Skin depth were calculated and correlated with irradiation.